Prebiotic and probiotic potential of fermented milk with cashew (Anacardium occidentale) by-products evaluated in in microbiome model - Herkenhoff, Marcos Edgar; de Medeiros, Igor Ucella Dantas; Garutti, Luiz Henrique Grotto; Salgaço, Mateus Kawata [UNESP]; Sivieri, Katia [UNESP]; Saad, Susana Marta Isay (Elsevier, 2024)
This study aimed to assess the functional attributes of the cashew by-product (CB) in fermented milk with the probiotic strain Lacticaseibacillus paracasei subsp. paracasei F19® (F19®) and the starter Streptococcus thermophilus ST-M6® (ST-M6®) using the Simulator of Human Intestinal Microbial Ecosystem (SHIME®). Two formulations of the fermented milk were assayed, in duplicates: Treatment 1 (T1, without CB) and Treatment 2 (T2, with CB). The strains behavior in the formulations and other bacterial groups of interest were assessed in SHIME®. The populations of the microbiota microorganisms and of the starter and probiotic strains were determined by PMA-qPCR. Metabolites produced in SHIME® reactors fermentation associated with nitrogen balance, antioxidant and phenolic compounds, and short-chain fatty acids (SCFA) were also measured. In SHIME®, both formulations had positive effects on the microbiota (an increase in Bifidobacterium spp. and Lactobacillus spp. and a decrease in Clostridium and Gamma Proteobacteria phyla). Considering these findings, probiotic fermented milk with F19®and ST-M6®, with or without cashew by-product, appears promising for a novel food product with enhanced nutrition, potentially classified as a synergistic synbiotic or at least a probiotic product.
Keywords: By-product; Cashew; Gut simulator; Intestinal microbiota; Prebiotic; Probiotics